2015
DOI: 10.1002/jcb.25395
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Human Mesenchymal Stem Cells Derived From Bone Marrow, Placenta, and Adipose Tissue as Sources of Cell Therapy

Abstract: Various source-derived mesenchymal stem cells (MSCs) with multipotent capabilities were considered for cell therapeutics of incurable diseases. The applicability of MSCs depends on the cellular source and on their different in vivo functions, despite having similar phenotypic and cytological characteristics. We characterized MSCs from different sources, including human bone marrow (BM), placenta (PL), and adipose tissue (AT), in terms of the phenotype, surface antigen expression, differentiation ability, prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
85
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 48 publications
1
85
0
1
Order By: Relevance
“…Konig et al [51] demonstrated that placental MSCs isolated from blood vessels were better than those from avascular tissues on supporting endothelial cell functions. Jeon et al [52] reported that placenta-derived MSCs retained a higher therapeutic efficacy than BMSCs and AMSCs in the hind-limb ischemic disease model. Moreover, our RT-PCR results showed a higher angiogenic cytokine expression in the same donor-derived PMSCs rather than UMSCs, which further indicated that the in-situ environment but not the development status might have some effect on the proangiogenic features of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Konig et al [51] demonstrated that placental MSCs isolated from blood vessels were better than those from avascular tissues on supporting endothelial cell functions. Jeon et al [52] reported that placenta-derived MSCs retained a higher therapeutic efficacy than BMSCs and AMSCs in the hind-limb ischemic disease model. Moreover, our RT-PCR results showed a higher angiogenic cytokine expression in the same donor-derived PMSCs rather than UMSCs, which further indicated that the in-situ environment but not the development status might have some effect on the proangiogenic features of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs derived from different tissues may have varied functional properties in spite of the similar morphologic characteristics and immunophenotypes, which make it complicated and confusing about what a source of MSCs to choose for a certain clinical purpose 15, 17 . Many comparative studies have been performed to investigate the proliferation, differentiation and immune regulation of MSCs derived from different tissues.…”
Section: Discussionmentioning
confidence: 99%
“…reported that BM-MSCs were also shown to undergo senescence at an earlier population doubling than the adipose and umbilical cord tissue-derived stem cells from equine tissue 25 . Placenta-derived MSCs were shown to have a lower potential to undergo adipogenesis but have a higher potential to undergo osteogenesis than BM-MSCs and Ad-MSCs 17 . However, the comparative adipogenic potentials of UC-MSC, Ad-MSC and BM-MSC are still controversial and the underlying molecular mechanism remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytological characteristics of MSCs vary according to their origin40. Placenta-derived MSCs were recently reported to possess better immunoregulatory properties than umbilical cord-derived MSCs41.…”
Section: Discussionmentioning
confidence: 99%